Geophysical mapping of the occurrence of platinum group elements in the main sulphide zone of the Great Dyke in Zimbabwe - Bernard Siachingoma; Dumisani John Hlatywayo; Vunganai Midzi; Leone Mare (Elsevier, 2023)
This work sought to establish the geophysical signature of platinum group elements in a mineralized sulphide host rock. It has been established that complex resistivity of rocks depends on frequency. The variation of resistivity magnitude and phase for the samples were taken for frequencies in the range 10−2 to 102 Hz. In the first part, the mathematical relationship between resistivity amplitude and phase with frequency was obtained based on the Cole-Cole model equation. A MATLAB Code based on the direct inversion of the apparent resistivity spectrum was used to extract the “Cole-Cole” parameters. In the second part an experimental procedure to obtain the data was designed and a discussion of the results obtained was made. Overally, the results confirm the model to be a good candidate for use in mapping the occurrence of platinum group elements in sulphide zones. Its frequency dependency parameter c is the critical anomaly detection parameter. Several efforts to solve this problem by other geophysical methods failed to yield the desired or useable results. The reason was the complex and inverse nature of the problem. The practical method chosen from a host of geophysical methods was complex resistivity measurements based on the “Cole-Cole model”. The knowledge gap being bridged in this study involves the use of this method to detect the base of the main sulphide zone.